Numerical Method for the Solution of a Hypersingular Integral Equation of the Second Kind - Kostenko, A. V. (Ukrains’kyi Matematychnyi Zhurnal, 2013)
А numerical method for the solution of a hypersingular integral equation of the second kind obtained as a generalization of the well-known method is proposed. The existence and uniqueness theorem is proved under additional assumptions. The rate of convergence of an approximate solution to the exact solution is obtained.